2016
DOI: 10.1016/j.appdev.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Does social–behavioral adjustment mediate the relation between executive function and academic readiness?

Abstract: Competitiveness Factors) under the National Strategic Reference Framework (QREN) attributed to the research project titled "Children's socio-emotional-cognitive school readiness: A longitudinal approach to its developmental course during preschool years" (PTDC/PSI-EDD/114527/2009). The authors are very grateful to the students who helped with data collection. Special thanks go to the children, families and preschool teachers who participated in the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 75 publications
1
27
1
Order By: Relevance
“…It is frequently suggested that research investigating the factors that contribute to a successful transition to school ought to follow child-by-environment models and consider both child and social-environmental influences (Palermo et al, 2007). Yet, research generally considers either child factors, such as EF, or social factors, such as peer or parent-child relationships, and rarely bridges these two sets of influences (Baptista et al, 2016). Likewise, there is mounting interest in the early social factors that promote child EF on one hand, and in EF's contribution to school achievement on the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…It is frequently suggested that research investigating the factors that contribute to a successful transition to school ought to follow child-by-environment models and consider both child and social-environmental influences (Palermo et al, 2007). Yet, research generally considers either child factors, such as EF, or social factors, such as peer or parent-child relationships, and rarely bridges these two sets of influences (Baptista et al, 2016). Likewise, there is mounting interest in the early social factors that promote child EF on one hand, and in EF's contribution to school achievement on the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…For example, early mathematics achievement predicts later reading achievement as strongly or more strongly than early reading achievement (Duncan et al., ). Similarly, children's behavior can predict their achievement (e.g., Duncan et al., ) and may also mediate initially observed relations between EF and achievement (Baptista, Osório, Martins, Verissimo, & Martins, ; Vitiello, Greenfield, Munis, & George, ). Yet behavior has only occasionally been included as a potential confound when examining predictive relations with specific EF processes (McClelland et al., ).…”
Section: Hypothesized Contributions Of Ef To Achievement and Behaviormentioning
confidence: 97%
“…In this paper we aim to explore: (1) predictors of children's socio-emotional skills and behaviour, and 2 There is a small corpus of studies (Doctoroff et al 2016;Baptista et al 2016 . Following these studies, we propose the first hypothesis: (1) children's mathematics performance in preschool will predict their socio-emotional skills and behaviour at entry to school.…”
Section: Aimsmentioning
confidence: 99%